The role of the plasmid-mediated fluoroquinolone resistance genes as resistance mechanisms in pediatric infections due to Enterobacterales - Logan, Latania K.; Coy, Laura Rojas; Pitstick, Claire E.; Marshall, Steven H.; Medernach, Rachel L.; Domitrovic, T. Nicholas; Konda, Sreenivas; Qureshi, Nadia K.; Hujer, Andrea M.; Zheng, Xiaotian; Rudin, Susan D.; Weinstein, Robert A.; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Fluoroquinolones (FQs) are not commonly prescribed in children, yet the increasing incidence of multidrug resistant (MDR)-Ent infections in this population often reveals FQ resistance. We sought to define the role of FQ resistance in the epidemiology of MDR-Ent in children, with an overall goal to devise treatment and prevention strategies. Methods A case-control study at 3 children’s hospitals was performed. Cases had infections by FQ susceptible, β-lactamase-producing (bla)-Ent harboring a non- or low-level expression of PMFQR genes(PMFQS-Ent). Controls had FQR infections due to bla-Ent with expressed PMFQR genes(PMFQR-Ent). We sought bla genes by PCR or DNA assay and PMFQR genes by PCR. Whole genome sequencing(WGS) was additionally performed on PMFQS-Ent positive isolates. Demographics, comorbidities; and device, antibiotic, and healthcare exposures were evaluated. Predictors of infection were assessed. Results Of 170 bla-Ent isolates, 85(50%) were FQS; 23(27%) had PMFQR genes (PMFQS cases). 85(50%) were FQR; 53(62%) had PMFQR genes (PMFQR controls). The median age for children with PMFQS-Ent and PMFQR-Ent were 4.3 and 6.2 years, respectively. Of 23 PMFQS-Ent, 56% were Klebsiella spp. and of 53 PMFQR-Ent, 76% were E. coli. The most common bla and PMFQR genes detected in PMFQS-Ent were blaSHV-ESBL(44%) and oqxAB(57%), and in PMFQR-Ent were blaCTX-M-1-group-ESBL(79%) and aac(6’)-Ib-cr(83%). WGS of PMFQS-Ent revealed the additional presence of mcr-9, a transferable polymyxin resistance gene, in 47% of isolates, along with multiple plasmids and mobile genetic elements propagating drug resistance. Multivariable regression analysis showed children with PMFQS-Ent infections were more likely to have hospital onset infection (OR 5.7, CI 1.6-22) and isolates containing multiple bla genes (OR 3.8, CI 1.1-14.5). The presence of invasive devices mediated the effects of healthcare setting in the final model. Differences in demographics, comorbidities, or antibiotic use were not found. Conclusions Paradoxically, PMFQS-Ent infections were often hospital onset and PMFQR-Ent infections were community onset. PMFQS-Ent commonly co-harbored multiple bla and PMFQR genes, and additional silent, yet transferrable antibiotic resistance genes such as mcr-9, affecting therapeutic options and suggesting need for address infection prevention strategies to control spread. Control of PMFQS-Ent infections will require validating community and healthcare-based sources and risk factors associated with acquisition.